The effects of purslane consumption on blood pressure, body weight, body mass index, and waist circumference: a systematic review and meta-analysis of randomised controlled - Behnaz Narimani; Mohammad Reza Amini; Fatemeh Sheikhhossein; Camellia Akhgarjand; Mohammad Gholizadeh; Moein Askarpour; Azita Hekmatdoost (Journal of Nutritional Science, 2023)
The effects of purslane consumption on anthropometric measurements and blood pressure have been studied in numerous experiments. However, the research findings conflict with one another. In order to assess the impact of purslane on weight, body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), and diastolic blood pressure (DBP), this meta-analysis was carried out. Up until February 2023, PubMed, Web of Science, Scopus, Google Scholar, and the reference lists of the identified pertinent randomised controlled trials (RCTs) were all searched. The random-effects model was used to calculate the effect size and then to describe it as a weighted mean difference (WMD) and 95 % confidence interval (CI) (CRD42023427955). The systematic review was able to incorporate seven RCTs. Meta-analysis showed that purslane significantly decreased body weight (WMD): −0⋅73 kg, 95 % confidence interval (CI): −1⋅37, −0⋅09, P=0⋅025), BMI (WMD: −0⋅35 kg/m2, 95 % CI: −0⋅64, −0⋅07, P=0⋅016), and SBP (WMD: −3⋅64 mmHg, 95 % CI: −6⋅42, −0⋅87, P = 0⋅01), and for WC, there was no discernible effect (WMD: −0⋅86 cm; 95 % CI, −1⋅80 to 0⋅07; P = 0⋅06) and DBP (WMD: −0⋅36 mmHg; 95 % CI, −1⋅75 to 1⋅03; P = 0⋅61). Purslane consumption, especially in participants with a BMI of <30, might play a role in decreasing SBP, body weight, BMI, and WC. Purslane consumption significantly reduced body weight, BMI, and SBP; however, WC and DBP did not experience a reduction. More investigation is needed to verify the impact of purslane consumption on anthropometric parameters and blood pressure.